Mathematics for elementary school teachers - Bassarear, Tom. (Boston : Houghton Mifflin, 2001)
Foundations for learning mathematics. Fundamental concepts. The four fundamental operations of arithmetic. Number theory. Extending the number system. Propỏtional réaoning...
Keywords: Mathematics; Mathematics -- Study and teaching (Primary)